The Influence Of Motivation And Work Skills On Work Productivity Of Yakes Telkom Makassar Employees - Nurfasila, Nurfasila; Muh Nur R; Andi Risfan Rizaldi (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the influence of motivation and work skills on the work productivity of Yakes Telkom Makassar employees. This research was conducted using a quantitative approach and data collection techniques through questionnaires. This research uses a non-probability sample, namely a saturated sample, where the entire population is sampled, namely 32 respondents at Yakes Telkom Makassar. The analysis technique used in this research is an interactive model with respondents, where the interpreted data is then regulated using data analysis techniques with SPSS version 25. The results of this research show that the Motivation variable (X1) has a significant influence on employee work productivity (Y). work skills (X2) do not have a significant influence on employee work productivity (Y).